Lumbar work and posture in pole-vaulters - Pomés, T.; Sust, F.; Turmo, A.; Til, L. (Archivos de medicina del deporte, 2008)
Introduction: Pole-vault athletes need a specific physical preparation that includes strengthening of the paravertebral lumbar muscles to prevent the lumbalgias that this group of athletes often suffer, limiting their return to training or competition Objectives: The aim of the study is to improve the lumbar strength with specific training of this area and analyze the changes that this training produces on the posture of three athletes. Material and methods: We studied three pole-vaulters of high performance for 2 months. All were males aged 19, 20 and 29. Before beginning lumbar work, a stabilometric static test (Satel system) and a test for assessing the lumbar strength baseline (MEDX system) were performed. Lumbar work for 8 weeks consisted of a specific eccentric muscular workout with the MEDX system once a week, with a starting load of 50% the maximum muscular strength recorded in the first evaluation test. Midway through the study, the athletes had an additional stabilometric static test. Upon completion of the 8 weeks a static stabilometric test and a lumbar test post-work were performed once again. Results: The values of lumbar strength in the pole-vaulters studied at the beginning of the study were higher than the mean for the same sex and age of this population of athletes. After training, and increase of 25% of the lumbar strength was observed, with the athlete feeling of more stability and without relapse during the 6 months following the reinforcement work. Stabilometric data do not show significant changes reflecting a better overall stability due to improved lumbar strength. Although there are intra-subject changes, values between individuals cannot be compared given the variability of the data and the small sample of athletes. Conclusions: Lumbar work with Medx in pole-vaulters is a good way to increase lumbar strength and prevent lumbalgias without changing postural parameters